2020
DOI: 10.1177/0890117120906971
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perspectives on the Dismissal of Vaccine-Refusing Families From Pediatric and Family Care Practices

Abstract: Purpose: Dismissal of families who refuse mandated childhood vaccines from pediatric practices has become more common among US pediatricians over the past 2 decades. While nurses (registered nurses [RNs] and advanced practice registered nurses [APRNs]) often are the first health-care professional to encounter parents’ vaccine hesitancy and serve as a primary source of information, there are no published data on nurses’ perspectives on dismissal as a response to vaccine refusal. This study examined nurses’ pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…2% or less of all HCP groups reported they preferred to no longer seeing VH patients/clients. This is in contrast to studies from the US ( 16 18 ) showing that the majority of physicians who responded to similar questions would prefer not to counsel VH patients and that they wished that VH patients would no longer come to their practice ( 49 51 ).…”
Section: Discussioncontrasting
confidence: 84%
“…2% or less of all HCP groups reported they preferred to no longer seeing VH patients/clients. This is in contrast to studies from the US ( 16 18 ) showing that the majority of physicians who responded to similar questions would prefer not to counsel VH patients and that they wished that VH patients would no longer come to their practice ( 49 51 ).…”
Section: Discussioncontrasting
confidence: 84%
“…experience vaccine hesitancy. Nurses are reported to consider the childhood vaccines recommended by the CDC as necessary for public health 18 . Nurses are often in the unique position of providing advice regarding vaccines in their formal practice areas and daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Among physicians who reported that they dismiss families, 18% reported that parents often or always change their minds and agree to vaccination (48% reported ‘sometimes’). A survey among a convenience sample of 488 US primary care nurses, most of whom were advanced practice providers, showed that 28% agreed or strongly agreed they would dismiss families who refuse all vaccines, and 12% would dismiss families for refusal of some but not all vaccines [79]. Thirty-nine percentage disagreed or strongly disagreed with dismissing families who refuse all vaccines, and 50% disagreed or strongly disagreed with dismissal for refusal of some but not all.…”
Section: Interventions To Address Vaccine Hesitancymentioning
confidence: 99%